(untitled) (مجلة العلوم الإنسانية والتطبيقية, 2018)
Background:- Helicobacter pylori ( H. pylori ) is one of the most frequent bacterial gastric pathogen in different parts of the world. In developing countries the infection can be almost ubiquitous, whereas in industrialized countries H. pylori infects around 30-50 % of adults. The risk of being colonized by H.pylori depends on geographic area, socioeconomic status and age of the host. Now, H. pylori has been associated with the most of gastro duodenal diseases. Aims:- To find out the prevalence of (IgG) antibodies of the gastric bacteria H.pylori. To correlate with the risk factors in voluntary asymptomatic healthy blood donors attending Central Blood Bank in Tripoli city. Materials & Methods:- A Blood sample of (175) adult healthy blood donors (50 Females, 125 Males mean age 35 years), anti-H.pylori IgG seroprevalence were determined with the ELISA method (Biotech USA), questionnaire covering Sociodemographic variables were completed by interview. Results:- The overall prevalence of H.pylori was 85.1% in the healthy Blood donors, there was a gradual increase with age, and no statistical difference between genders. Conclusion:- In Tripoli region, H.pylori detection in those adult healthy blood donors was high of aged 25-40 years, which might be related to the socioeconomic status, domestic crowding and the source of drinking water as a major risk factors for H.pylori infection. Also we confirm that as a non- invasive method, the serologic test such as (ELISA) is a useful technique to detect H.pylori infection among healthy population. However, larger studies in other regions of Libya should be conducted to confirm our study findings.